Distant suffering : on mediated suffering and health care - Jill Witney Åhs (2024)
This thesis examines distant suffering, or when suffering of others who are far away is mediated or conveyed. Distant suffering often refers to when popular media or humanitarian campaigns display images of people suffering amidst catastrophes in faraway lands. Such displays of distant suffering can have negative implications for those who are suffering and those observing the images. In this digital age, an image of suffering can be easily transmitted widely and instantly. Also, use of telehealth technologies has now become common practice in settings globally. During telehealth care, providers may encounter the suffering of patients far away. The aim of this thesis is to explore the concept of distant suffering and its relevance for health care.Through four papers, distant suffering is explored empirically and theoretically. The first paper (Study I) explores telecare providers' experiences encountering patients who are suffering. The second paper (Study II) explores how suffering is perceived in humanitarian images. The third study (Study III) examines conceptualizations of distance in providers' encounters with suffering in telecare. The fourth paper (Study IV) is a concept analysis, advancing theoretical development of distant suffering and its relevance in health care.Providers' encounters with suffering in distant care were experienced as loose connections, both in compromised technology and compromised emotional connection. Insecurity in digital practice, inaccessibility of tools, and conviction in the value of telehealth care arose in providers' experiences (Study I). In humanitarian images, perceived suffering was described in themes of decoded emotions and their physical expressions, a nexus of uncertainty and vulnerability, and through relatability or resonance with what was observed (Study II). In tele- care, distance presented as physical and emotional distance, where, for some patients, telecare may not be suitable, while for others it is a bridge to accessing care (Study III). The concept of distant suffering includes attributes of mediated faraway suffering, a "recognizer" who observes it, and a potential moderator (Study IV). Through shared social and cultural understandings, consequences of distant suffering may include moral or emotional responses, inaction, or pity.Distant suffering is greatly relevant for both patients and health care providers. It is an important area of inquiry to further understanding, from its origins in humanitarian images to its presence via modern telecare, to ensure patients and providers have successful and rewarding distant health care encounters.List of scientific papersI. Åhs, J. W., Ranheim, A., Eriksson, H., & Mazaheri, M. (2023). Encountering suffering in digital care: a qualitative study of providers' experiences in telemental health care. BMC health services research, 23(1), 418. https://doi.org/10.1186/s12913-023-09367-xII. Åhs, J. W., Eriksson, H., & Mazaheri, M. Perceived suffering in humanitarian images: a photo-elicitation. [Submitted]III. Åhs, J. W., Ranheim, A., Mattelin, E., Eriksson, H., & Mazaheri, M. (2023). Distance in Distant Care: Qualitative Content Analysis of Providers' Experiences in Tele-Mental Care. Journal of medical internet research, 25, e38568. https://doi.org/10.2196/38568 IV. Åhs, J. W., Eriksson, H., & Mazaheri, M. (2024). Distant suffering: A concept analysis. International journal of nursing studies, 151, 104672. https://doi.org/10.1016/j.ijnurstu.2023.104672